Polysubstance Use in Cannabis Users Referred for Treatment: Drug Use Profiles, Psychiatric Comorbidity and Cannabis-Related Beliefs - Connor, Jason P.; Gullo, Matthew J.; Chan, Gary; Young, Ross M.; Hall, Wayne D.; Feeney, Gerald F. (Frontiers in Psychiatry, 2013)
Background: Population-based surveys demonstrate cannabis users are more likely to use both illicit and licit substances, compared with non-cannabis users. Few studies have examined the substance use profiles of cannabis users referred for treatment. Coexisting mental health symptoms and underlying cannabis-related beliefs associated with these profiles remains unexplored. Methods: Comprehensive drug use and dependence severity (Severity of Dependence Scale- Cannabis [SDS-C]) data were collected on a sample of 826 cannabis users referred for treatment. Patients completed the General Health Questionnaire (GHQ-28), Cannabis Expectancy Questionnaire (CEQ), and Cannabis Refusal Self-Efficacy Questionnaire (CRSEQ) and Positive Symptoms and Manic-Excitement subscales of the Brief Psychiatric Rating Scale (BPRS). Latent class analysis (LCA) was performed on last month use of drugs to identify patterns of multiple drug use. Mental health comorbidity and cannabis beliefs were examined by identified drug use pattern. Results: A three-class solution provided the best fit to the data- (1) Cannabis and tobacco users (n = 176), (2) Cannabis, tobacco, and alcohol users (n = 498), and (3) wide-ranging substance users (n = 132). Wide-ranging substance users (3) reported higher levels of cannabis dependence severity, negative cannabis expectancies, lower opportunistic and emotional relief self-efficacy, higher levels of depression and anxiety, and higher manic-excitement and positive psychotic symptoms. Conclusion: In a sample of cannabis users referred for treatment, wide-ranging substance use was associated with elevated risk on measures of cannabis dependence, comorbid psychopathology and dysfunctional cannabis cognitions. These findings have implications for cognitive-behavioural assessment and treatment.